(untitled) - Đinh, Thị Hồng Nhung (Cần Thơ, 2019)
Action research in English language teaching has played a significant role in improving teachers’ quality as well as their professional development. This paper examines the perceptions of EFL teachers about the role of doing action research to improve their teaching quality. Both qualitative and quantitative, including questionnaires and interviews were use in this study. Sixty-five EFL teachers who are following an MA program at Can Tho University got involved in the study as participants. The findings revealed the positive perceptions of EFL teachers of doing action research. However, there were certain challenges faced by these lecturers with their action research practices. As a result, appropriate measures to tackle such challenges in the current teaching context regarding the roles of teachers and administrators are proposed.
Keywords: Phương pháp giảng dạy,Teaching methods